1999
DOI: 10.1128/jvi.73.8.6691-6699.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Baculovirus PE38 Protein Augments Apoptosis Induced by Transactivator IE1

Abstract: While studying apoptosis induced by baculovirus transactivator IE1 in SF-21 cells, we found that the levels of IE1-induced apoptosis were increased approximately twofold upon cotransfection with the baculovirus early pe38 gene. However, no apoptotic activity was observed in cells transfected with pe38 alone, even when placed under the control of a constitutive promoter. Thus,pe38 was able to augment IE1-induced apoptosis but was unable to induce apoptosis when expressed in SF-21 cells alone. PE38, the full-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For example, PE38 could ubiquitinate the actin-specific nuclear export protein exportin-6, ultimately facilitating the nuclear accumulation of actin (Stüven et al, 2003). Another possibility involves PE38's role in enhancing IE1-induced apoptosis (Prikhod'ko & Miller, 1999), a stress that could lead to the accumulation of actin within the nucleus (Luchetti et al, 2002), even though apoptosis is ultimately blocked (Clem, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PE38 could ubiquitinate the actin-specific nuclear export protein exportin-6, ultimately facilitating the nuclear accumulation of actin (Stüven et al, 2003). Another possibility involves PE38's role in enhancing IE1-induced apoptosis (Prikhod'ko & Miller, 1999), a stress that could lead to the accumulation of actin within the nucleus (Luchetti et al, 2002), even though apoptosis is ultimately blocked (Clem, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only HE65 and PE38 have been characterized previously. Functions ascribed to PE38 include acting as an early gene transactivator, a ubiquitin ligase, a factor in DNA replication and an enhancer of IE1-induced apoptosis (Imai et al, 2003;Kool et al, 1994;Lu & Carstens, 1993;Prikhod'ko & Miller, 1999). HE65 is an early gene product with similarity to the RNA ligase 2 nt binding pocket, but RNA ligase activity has not been confirmed experimentally (Becker & Knebel-Mörsdorf, 1993;Ho & Shuman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The insect-specificity of APETx3 is demonstrated by the complete inhibition of the inactivation of the insect Na V channels DmNa V 1 and BgNa V 1.1, and it is furthermore emphasized by the 10-fold difference in EC 50 values between mammalian (Na V 1.6) and insect (DmNa V 1) channels. This preference for insect Na V channels suggests that APETx3 can be used as an insecticide (34,35).…”
Section: Apetx3mentioning
confidence: 99%
“…Previous studies have also shown that AcMNPV-induced apoptosis of Sf21 cells is triggered by IE1, the product of the immediateearly viral gene ie1 (Prikhod'ko & Miller, 1996), and suppressed by P35 and inhibitor of apoptosis (IAP) proteins, which are encoded by the genomes of certain NPVs (Clem, 1997(Clem, , 2001). It has also been shown that IE1-induced apoptosis of Sf21 cells is augmented by the AcMNPV early gene product PE38 (Prikhod'ko & Miller, 1999). In addition, apoptosis induced by baculovirus infection has been shown to be associated with the activation of caspases (Bertin et al, 1996;Ahmad et al, 1997;LaCount & Friesen, 1997;Seshagiri & Miller, 1997;LaCount et al, 2000;Manji & Friesen, 2001).…”
Section: Introductionmentioning
confidence: 99%